1990
DOI: 10.1007/bf02277309
|View full text |Cite
|
Sign up to set email alerts
|

Name changes in fungi of microbiological, industrial and medical importance

Abstract: This is the fourth in a series of reports bringing changes in the names of fungi of microbiological, industrial and medical importance to the attention of workers in these fields. The series is sponsored by the Division of Mycology of the International Union of Microbiological Societies (IUMS) and prepared under the auspices of the International Commission on the Taxonomy of Fungi (ICTF). The first of this series of reports included an introduction to the series explaining the need for name changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Four strains of Rhizopus (class Zygomycetes, order Mucorales, family Mucoraceae), were studied, including 2 ofRhizopus microsporus var. rhizopodiformis (R. microsporus) and 2 ofRhizopus arrhizus (formerly called Rhizopus oryzae) (15 [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Four strains of Rhizopus (class Zygomycetes, order Mucorales, family Mucoraceae), were studied, including 2 ofRhizopus microsporus var. rhizopodiformis (R. microsporus) and 2 ofRhizopus arrhizus (formerly called Rhizopus oryzae) (15 [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…It was also observed that both the round and oval yeast forms could produce hyphae, and this led to the suggestion that the round and oval yeast forms and hyphae were simply stages in the life cycle of a single organism (383). The ability to induce the yeast to form mycelial elements paved the way for the unification of the two genera in 1986, with the acceptance of the species names Malassezia furfur (Robin) Baillon (including P. orbiculare, P. ovale, and M. furfur) and Malassezia pachydermatis (including P. pachydermatis) (79). Despite this, many workers maintained the use of the names P. ovale and P. orbiculare and continued to differentiate strains on the basis of cellular and colonial morphologies (128,288,402).…”
Section: Taxonomymentioning
confidence: 99%
“…In 1986, the weight of evidence led to the unification of the different morphological forms within the species M. furfur (79). However, the ability to grow very distinct colony variants from the same site on human skin led workers to define three serovars of M. furfur (101).…”
Section: Structure Physiology and Biochemistrymentioning
confidence: 99%
“…However, in 1986 they were recognized to be two forms of the same organism and were thus collectively named Malassezia (Cannon, 1986). Malassezia considered as a normal cutaneous inhabitant of skin in humans, animals and birds.…”
Section: Introductionmentioning
confidence: 99%